The structure of the fantastic narration and its enriching action in the narrative text: Stories (Nasser Salem Al-Jassim) sample - Jassem, Dr. Muhammad Jerry; Al-Rikabi, Mead Makki Faisl (Al-Adab Journal, 2021)
This is a critical study on the topic of fantastic in the stories of the Saudi writer Nasser Salem Al-Jassim, who has been issued eight groups and four manuscript groups, three printed novels and one manuscript,These groups are characterized by several features that formed the aesthetics of its texts and their diversity, especially their interest in fantastic employment in some of the narrative components that we singled out for this study. From concepts that are rooted in the public imagination.Not only that, but rather, in specific joints of its narrative content, it has employed the Saudi dialect to give the texts a great and profound meaning that brings them closer to the reader, and also gives them the status of credibility.The fictional location also contributed to this, and those places were depicted through the impressions of the characters, these impressions are only the repercussions of the personal contact with the place and its interaction in it, and thus the place contributed to reading the psychology of the characters and giving them the fantastic characteristic.For this purpose, this study will focus on examining the structures that have achieved the fantastic character of texts, namely the fantastic structure of the text, and the structure of fantastic space, as will be shown in its place.